Ājāda Hindera śesha laṛāi - Dāsa, Ramena (Mausumī Sāhitya Mandira, 1980)
On the role of the militant nationalist leader Subhash Chandra Bose, 1897-1945, in the formation of the Indian National Army to fight against the British on the northeastern border of India; a phase in the Indian freedom movement.